Congenital Talipes Equinovarus (CTEV) - Laloan, Richardo J.; Lengkong, Andreissanto C. (Universitas Sam Ratulangi, 2020)
Abstract: Congenital talipes equinovarus (CTEV) is a type of foot deformities characterized with hindfoot varus, adducted metatarsus, wide arched of the foot (cavus), and equinus. Its incidence is 1.2% per 1000 births annually. Around 80% of cases occur as idiopathic type and the remaining 20% is associated with other anomaly conditions. Genetic component is considered to play a role in the occurrence of CTEV. However, up to this day, there is no exact underlying etiology that defines the exact pathogenesis of CTEV. The evolving etiology nowadays is still multifactorial. Management of CTEV varies from non-surgical treatment to surgical treatment. A number of scoring and grading using qualitative and quantitative measurement are being used nowadays to assess the severity of CTEV because this deformity needs long-term follow-up due to its tendency to relapse.Keywords: congenital talipes equinovarus, clubfootÂ Abstrak: Congenital talipes equinovarus (CTEV), dikenal juga dengan true clubfoot, merupakan deformitas pada kaki yang ditandai oleh adanya bentuk varus kaki belakang, adduksi metatarsus, dan adanya bentuk lengkungan kaki yang lebar (cavus) serta equinus. CTEV merupakan salah satu dari deformitas kaki pada saat lahir dengan insidensi 1,2% per 1000 kelahiran hidup per tahunnya. Pada 80% kasus terjadi secara idiopatik dan 20% dikaitkan dengan kondisi-kondisi lain. Komponen genetik diduga berperan pada CTEV, namun, sampai saat ini, belum ada etiologi pasti yang menjelaskan patogenesis CTEV. Etiologi yang berkembang sampai saat ini bersifat multifaktorial. Tatalaksana pasien CTEV bervariasi mulai dari non-operatif maupun operatif. Sejumlah pengukuran kualitatif maupun kuantitatif telah dikembangkan untuk menilai keparahan CTEV berhubung kondisi deformitas ini membutuhkan follow-up jangka panjang karena mempunyai kecenderungan untuk relaps.Kata kunci: congenital talipes equinovarus, clubfoot